The effect of autoclaving method on sago starch as a functional food source: a review from a gastronomy perspective - Supriyadi, Edouard Aryadi; Azhari, Azril; Widianto, Nur (Surya Hijau Manfaat, 2024)
Starch is a carbohydrate that is a polymer of glucose, and consists of amylose and amylopectin. Starch is found abundantly in the gastrointestinal tract and is slightly fermented by the intestinal microflora. RS is often identified as a food starch that cannot be digested in the small intestine so that it functions properly for the health of the human body. This study aims to investigate the effect of autoclaving method on sago starch as a functional food source, with emphasis on gastronomic aspects. Through this approach, we can gain a more comprehensive understanding of the potential of sago starch in providing healthy and tasty food for consumers. This research method was carried out under the condition of modification of sago starch by autoclaving-cooling including modification cycles, among others: no cycle, one cycle, 2 cycles, and 3 cycles. The results showed T0 starch showed 1.26% and 3 cycles showed 5.62%. The best modification of RS starch is shown in the cycle process 3.